THE IMPLEMENTATION OF VILLAGE-OWNED ENTERPRISES POLICY IN WONOGIRI REGENCY - Fallenda Mahatva Dewi; Didik Gunawan Suharto (NATAPRAJA, 2020)
This research aimed to identify supporting and inhibiting factor in the implementation of Village-Owned Enterprise (BUMDes) policy in Sumberejo Village, Batuwarno Sub District, Wonogiri Regency. The approach used in this study was descriptive qualitative research. Data were obtained from the result of interview, documentation, and observation. Interview was conducted with the officials representing Village Community Empowerment Office of Wonogiri Regency and the officials Sumberejo Village. Documentation related to BUMDes of Sumberejo Village. Observation was conducted by seeing situation and condition in Sumberejo Village environment and BUMDes. The result of research showed that the supporting factor in the implementation of BUMDes policy included: communication; disposition; characteristics of the the implementing agencies and economic, social and political conditions. Meanwhile, the inhibiting factor included resources (HR or human resource and budget resource); bureaucratic structure; and policy standard and objectives. Supporting factors can encourage the development of BUMDes and increase the profit, despite some limitations. The factors inhibiting BUMDes policy generates some problems to BUMDes, so that its profit percentage and contribution to PADes (Original Village Income) have not been optimal yet and is fluctuating. Edward III’s, and Van Meter and Van Horn’s implementation model theory used to analyze BUMDes policy in this study evidently are the factors affecting the implementation of BUMDes policy, in the form of supporting and inhibiting factors.